Levels of Physical Activity in Children and Adolescents with Type 1 Diabetes in Relation to the Healthy Comparators and to the Method of Insulin Therapy Used - Ewelina Czenczek-Lewandowska (International Journal of Environmental Research and Public Health, 2019)
Given the fact that physical exertion leads to blood glucose fluctuations, type one diabetes mellitus (T1D) may potentially constitute a barrier for obtaining a sufficient amount of exercise. The main purpose of the study was to compare the level of physical activity between children with T1D (n = 215) and healthy controls (n = 115) and to assess the physical activity of the study group in relation to the applied method of insulin therapy, i.e., the use of insulin pen vs. insulin pump. The level of physical activity was assessed with a hip-worn tri-axial accelerometer (ActiGraph GT3X+) used by the subjects for an uninterrupted period of seven days. Children with T1D had significantly lower median values of total time of moderate (213.3 vs. 272.1 min), vigorous (135.3 vs. 19.6 min) and moderate-to-vigorous (347.4 vs. 467.4 min) physical activity compared to healthy peers respectively, (p < 0.001) in all cases. In addition, the total median number of steps was significantly lower (53,631 vs. 67,542 steps), (p < 0.001). The method of insulin therapy was not associated with significant differences in physical activity level (p > 0.001). The level of physical activity in children and adolescents with T1D is lower than in their healthy peers and does not depend on the insulin therapy method.